Economic and shariah determinants of financial technology innovation in cryptocurrencies / Muneer Maher Mahmoud Ahmad - Muneer Maher, Mahmoud Ahmad (2019)
This study aims to clarify and reveal the economic and shariah determinants of financial technology in the field of monetary innovations. To achieve this, the study dealt with the subject of financial technology - which is considered a new knowledge branch – to tackle its different dimensions like its reality, importance, fields, and effects for better understanding of its application. Researcher addressed the urgent need to regulate and standardize the technological innovations like cryptocurrency, and the need to follow the determinants both from shariah, economic and technical aspects to achieve safe contracting and transitioning among dealers. Following the proposed determinants would be in help of the central authority’s decision-making process as well. The right application of the determinant will help avoid losses and damages resulting from lack of readiness and imbalance of justice among dealers, the procedures are represented in the criteria’s of effectiveness and shari’ah compliance included in the dissertation, the latter criteria’s for technological monetary innovations are considered a necessity for achieving financial objectives in a desired Islamic economy. The researcher used the analytical inductive method in this qualitative study to reveal clear controls and criteria’s to be used in determining the appropriateness of technological financial innovations for approval by the central authorities. Researcher presented an illustrative case of the encrypted virtual currencies (The study model of the dissertation) due to their wide prevalence in the time of writing the study, however the study is a clear example of the technological innovations of money, the researcher has reached the following main results: The use of financial technology in money should be under the full control of the ruling authorities with fair terms for all parties because of the security and centrality of money and the fact that it is a public matter and must be subject to the monetary policy ruled by the authorities for general well-fair and any economic reforms. The issuance of money from a private institution is a violation of this purpose and a blatant attack on the social body and is a confiscation of the community rights of the benefits of currency issuance, also the centralization of information resulting from the centralization of the issuance of money is a top priority risk that must be maintained from abuse, while the encrypted virtual currencies issued by private parties and without a cover from real assets is a dangerous violation of these principles of justice, while not following shari’ah rules and economic criteria’s of effective currency resulted in a significant financial losses during the past decade with little economic benefit.